Temperament, optimism and a tendency to take risks in pilots and professional drivers - Baran, Paulina Maria (Studia Psychologica: Theoria et praxis, 2011)
The main aim of this article is to present the results of the research carried out on pilots and professional drivers about their tendency to take risks. The studies have explored the relationship between temperamental characteristics, level of optimism and a tendency to take risks in groups of pilots and professional drivers. Moreover, there was an attempt to characterize and compare the two professional groups in terms of the variables tested. The results showed no relationship between the level of optimism and a tendency to take risks in both groups. However, there has been shown associations between temperamental characteristics and a tendency to risky behavior and some significant differences between groups in a range of variables examined. Finding determinants of risk taking is today one of the major issues in the area of transport psychology, among other things, from the viewpoint of increasing the level of safety of travelling and the mobility of people around the world.